PENGARUH KOMUNIKASI INTERPERSONAL TERHADAP KOMITMEN KERJA PEGAWAI DI DINAS PENDIDIKAN DAN KEBUDAYAAN PROVINSI SUMATERA BARAT - RIKO PUTRA YUSBAR (Jurnal Bahana Manajemen Pendidikan, 2017)
The purpose of this study to obtain information about interpersonal communication, commitment, interpersonal communication and influence on the commitment of employee in the Dinas Pendidikan dan Kebudayaan Provinsi Sumatera Barat. The hypothesis of this study is communicates interpersonal significantly influence employee commitment. The study population was all employees who work the Dinas Pendidikan dan Kebudayaan Provinsi Sumatera Barat amounted to amounted to 230 people with a sample of 38 people using Proportional Stratified Random Sampling technique. The research instrument used was a questionnaire that has been in testing the validity and reliability. In general, the data analysis showed (1) an employee interpersonal communication that are in both categories, namely 87.16% (2) the commitment of employees working at the high category is 87.44%, (3) there is a significant effect of variable x to variable y ie 19.8%.